Kulturowy charakter czasu i przestrzeni. Analiza średniowiecznego i wczesnorenesansowego elitarnego budownictwa mieszkalnego i obronnego w Irlandii - Kiarszys, Grzegorz (Folia Praehistorica Posnaniensia, 2018)
The main goal of my PhD thesis is socio-cultural interpretation of architectural space in Medieval Irish castles. Furthermore, I intend to discuss the way archaeologists think and write about the past. The first part of the PhD thesis is an attempt to define my own understanding of concepts such as memory, tradition, culture, society, social order, power, architecture, cultural spacetime, language, and narration. The idea of the past is not only concerned with past events. Its picture is created by present perception and future expectations. These play a key role in the way in which we create cause and effect relationships, which is to provide foundations for the structure of past narratives. Consequently, our idea of the past and its meaning shifts dynamically according to our expectations and social context. This is also fundamental for constructing cultural identity. In archaeology, this problem has a form of relationships between archaeological data and the past. I believe artefacts can only be seen as an inspiration for different pictures of the past created by archaeologists. They may have lost their connection with the past and become an element of the present context. The second part of my PhD thesis concerns social relations in Medieval society. This is based upon analysis of the elite architecture in Ireland. The most important research issueconcerns the meaning of architectural space in castles. This comprises the followingquestions: How did the architecture reflect social status of its inhabitants? In what ways might the arrangement of the interior have influenced social practice? What was the perception of elite architecture by non-elite groups? The cultural construction of architectural time and space is related to social order and group identity. I believe that searching for meaning of the symbolism involves thinking about castles as a metaphor of theatre or stage of social life. We need to understand not only the symbolic meaning of every individual detail but also their mutual relationships and purpose. There are approximately 3,500 castles in Ireland surviving to the present day. The late Medieval Ireland was possibly the most heavily castellated part of Western Europe. Numerous and constant wars between the Anglo-Norman aristocracy and the indigenous Gaelic Chieftains led to social unrest and anxiety. It was also one of the main reasons for the rapid development of castles. History of architecture can be considered as a history of human society. Changes of style and design are in fact often related to social conflict, which not only gives impetus to the development of the art but can also be destructive. Irish castles are indicative of such conflict.